Perlindungan Hukum Terhadap Korban Kekerasan Seksual dalam Rangka Mewujudkan Keadilan Restorative Justice - Adelia Wulandari, Aulia (Proceedings Series on Social Sciences & Humanities, 2024)
Legal protection is very important and affects justice for all Indonesian citizens. According to the viewpoint of the concept of restorative justice, handling crimes that occur is not only the responsibility of the state but also the responsibility of the community. Therefore, the concept of restorative justice is built based on the notion that crimes that have caused losses must be recovered, both losses suffered by the victim and losses borne by the community. Various sensitive issues afflict the lives of women, including crimes of sexual violence (sexual violence) and sexual harassment (sexual harassment). Women are very vulnerable to becoming victims of crime in the field of decency. The efforts of legal protection agencies or advocacy institutions in creating good law enforcement really need supporting factors in order to create such legal protection properly and effectively.